KELAYAKAN EKONOMI PELEBARAN JALAN ALTERNATIF PUNCAK KECAMATAN MEGAMENDUNG DAN CISARUA - Raka Surya Pradana; M. Ridha Al Mustaf (Universitas Tangerang Raya, 2026)
The Puncak area, particularly in Megamendung and Cisarua Subdistricts, is one of the main transportation corridors in Bogor Regency, serving both as a major tourist destination and as a regional connector. High traffic volumes, especially during weekends and holiday seasons, often result in severe congestion, leading to increased vehicle operating costs, excessive fuel consumption, longer travel times, and reduced user comfort. One potential solution is the widening of alternative roads; however, such an investment requires a comprehensive economic feasibility study to ensure that the benefits outweigh the costs. This study aims to evaluate the economic feasibility of widening alternative roads in the Puncak area using a cost–benefit analysis framework. The methods applied include the calculation of Net Present Value (NPV), Benefit Cost Ratio (BCR), and Internal Rate of Return (IRR). The data analyzed cover construction investment costs, vehicle operating costs (VOC), travel time savings (value of time), and other potential economic benefits. The results indicate that the proposed project yields a positive NPV, a BCR greater than 1, and an IRR exceeding the reference interest rate, demonstrating that the road widening project is economically feasible. Nevertheless, social, environmental, and spatial planning aspects should also be considered to ensure sustainable implementation.